Surface Layer Modification by Cryogenic Burnishing of Al 7050-T7451 Alloy and Validation with FEM-Based Burnishing Model - KAYNAK, YUSUF (ELSEVIER SCIENCE BV, 2015)
As one of the chipless machining processes, burnishing has been performed on manufactured components as the final operation to improve the surface integrity, including reduced surface roughness and increased surface and subsurface hardness. Refined surface layers with ultra-fine grains or nano-grains could be generated during the burnishing process due to imposed severe plastic deformation and the associated dynamic recrystallization (DRX). These harder layers with compressive residual stresses induced by the burnishing process also provide added benefits by enhancing wear/corrosion resistance and increasing the fatigue life of the components. The research findings presented in this paper show the effects of cryogenic burnishing with roller burnishing tool on Al 7050-T7451 alloy, using liquid nitrogen as the coolant. Burnishing forces and temperatures are measured to compare the differences between dry and cryogenic burnishing. Higher tangential forces and lower temperatures are observed from cryogenic burnishing due to the work-hardening and the rapid cooling effects introduced by cryogenic burnishing. Also, refined layers with nano-grains (grain size of approximately 40 nm) are formed in the cryogenically burnished surface, in which an average hardness increase of 9.5%, 17.5% and 24.8% within the 200 mu m depth are achieved in comparison with the hardness values obtained from dry burnishing, at the corresponding burnishing speeds of 25, 50 and 100 m/min. A finite element model (FEM) is developed to simulate the burnishing forces and temperatures for validation of the experimental results, based on the modified Johnson-Cook flow stress model combined with the constitutive equations concerning DRX. Good agreement is obtained between the predicted and experimental results. (C) 2015 The Authors. Published by Elsevier B. V. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/).
Keywords: Cryogenic burnishing; Nano structure; Hardness; FEM; SEVERE PLASTIC-DEFORMATION; MO BIOMEDICAL ALLOY; ALUMINUM-ALLOY